PENINGKATAN KETERAMPILAN MENULIS DESKRIPSI MENGGUNAKAN PETA KONSEP DI KELAS IV S D N 09 BUNGUS - Darnis Arief (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2015)
Description writing skills of students is low. They have not been able to describe objects clearly. An explanation of an object has not been systematic and often commute. In addition, there are temporary paragraphs consists of only one sentence. Sentences are used not been effective so elusive. This research is a classroom action research conducted two cycles. Each cycle consists of planning, implementation, observation, and reflection. Use of concept maps are proven to improve students' skills in writing a description. The results of student writing in the first cycle an average of 62 including categories enough, on the second cycle increased to 77, including both categories.